Kesesuaian Lahan dan Faktor-Faktor yang Mempengaruhi Implementasi Penataan Ruang di Sub Das Gunting Kabupaten Jombang - Maulana, Karunia Kinantar; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Gunting sub watershed is a part of the Brantas river basin in East Java. The flow includes 5 districts in Jombang, which entailedÂ  vital role for Jombang regency because of the agricultural rice centers in the downstream and the plantation in upstream. However, the incidence of floods, landslides, and drought seemed to be an annual event in this region. Land pressure and economic needs led to massive misuses of land in Gunting sub watershed. this study aims to assess land suitability by measuring the extent of land misuses then identify the factors that affect the implementation of spatial planning by using quantitative descriptive approach. spatial analysis and SWOT analysis become the main techniques to answer the research objectives. The results of Landsat 8 satellite image interpretation show that the largest land use in Gunting sub-watershed is agricultural area of 12095.6 hectares from total area of 36 884 Ha. Meanwhile, the results of SWOT analysis known EFAS score (2.65) is greater than the score of IFAS (1.9). This suggests that the mechanism of land use in Gunting sub-watershed is more dominant influenced by external factors rather than internal factors.